PEMANFAATAN LAHAN SEMPIT UNTUK MEMENUHI KEBUTUHAN SEHARI-HARI DI DESA JLEGIWINANGUN KECAMATAN KUTOWINANGAN KABUPATEN KEBUMEN (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Food security starts from the level of family food security by utilizing the land around the house to produce food crops, does not require a lot of planting media, and can also reduce household costs. What is more important is being able to produce food without buying it on the market. In general, yard land in urban areas has a narrow area. Likewise, the condition of the yard in Jegliwinangun Village, Kec. Kutowinangun, Kab. Kebumen, with optimal and planned use of yard land, it is hoped that the community can meet the family's food needs and can also obtain additional income outside of income from the main job. Mentoring was carried out for 8 months. Location: Jegliwinangun Village, Kuthowinangun District, Kebumen Regency, which was attended by around 60 participants consisting of Village officials, the PKK Mobilization Team, Representatives, the community and the young generation of Jegliwinangun Village. The method used is to provide socialization followed by a demonstration on how to plant on narrow land as an effort to meet daily needs. The activity took place on March 5 2024. Based on the results of the activities that have been carried out, it shows that residents are enthusiastic about becoming more productive and enthusiastic about entrepreneurship and farming.